Feasibility of Engaging Community Healthcare Workers to Identify and Enhance Subfertility Care in The Northern Province, Sri Lanka. - Raguraman, S.; Balagobi, B.; Kumaran, S.; Kiruththiga, T.; Shanmuganathan, Y.; Kanesamoorthy, S.; Arulkumaran, S. (The Jaffna Medical Association, 2024)
Subfertility is a significant global reproductive health challenge affecting approximately 1 in 6 individuals worldwide. Despite having a comprehensive healthcare system, Sri Lanka still faces challenges in providing timely and effective fertility care. We propose integrating Community Health Workers (CHWs) into the healthcare system to address these challenges. The present study aimed to assess the acceptability, appropriateness, and feasibility of the Community Health Worker Facilitated Fertility Care (CHWFFC) model in the Nallur MOH area, Jaffna, Sri Lanka. The intervention, conducted over six months, demonstrated promising outcomes, including positive stakeholder feedback, reduced PHMs’ workload, and an effective identification and referral system for subfertile couples.